Rise of the New Middle Class in Nepalese Politics and Its Relevance to Global Politics - Lamsal, Chakrapani (Tribhuvan University Journal, 2024)
The study is focused on the evolution of the middle class in Nepal from a political perspective. It is an interdisciplinary and mixed method of study. The new middle class in this study is defined in a multi-disciplinary approach specific to education, consciousness, and activeness. The study argues new middle class in Nepal is raised in politics for the fulfillment of the issues and interests of a new generation that are missed by the established political parties. It further argues it is raised with a specific time, and context favored by its size and issues. Their unique issues of politics and tools of democratization favour to be an alternative political party but to be tested in their practices. The objective of the study is to shed light on the rise of the new middle class in Nepalese politics and its significance in global politics. The study is based on secondary sources and document analysis as well as non participant observation methods is used. It concludes that emerging parties can be an alternative agency of the new middle class if the new groups come together on common departure, agency, and issues with loyalty on their agenda and practices consistently.